Hubungan Antara Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Pre Operasi Histerektomi Di Instalasi Bedah Sentral Rsud Dr Saiful Anwar Malang - Nurit paramita sandi Nurit; Achmad Dafir Firdaus; Reny Tri Febriani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction: Hysterectomy surgery can cause various kinds of anxiety for patients. Family support can help patients deal with the stress and anxiety of hysterectomy surgery. This study aims to determine the relationship between family support and anxiety levels in preoperative hysterectomy patients at the Central Surgical Installation of RSUD dr Saiful Anwar Malang. Methods: Research method descriptive analytic with cross-sectional approach l. The population and sample of this study were 33 respondents with total sampling techniques. The research instrument was a questionnaire on family support and preoperative anxiety levels using the Hamilton Anxiety Rating Scale (HARS). Results: The results showed that most respondents (84.8%) had family support, and 42.4% had anxiety levels in the mild and moderate categories in preoperative hysterectomy patients. Analysis with the Spearman Rank test with α = 0.05 obtained p value = 0.030 or p < 0.05 showed that there was a relationship between family support and anxiety levels in preoperative hysterectomy patients at the Central Surgical Installation of RSUD dr Saiful Anwar Malang with. Conclusion: Family support affects the anxiety of pre-hysterectomy patients because family support can help patients deal with the stress and anxiety caused by hysterectomy surgery. The better the family support, the lower the anxiety levels of patients after preoperative hysterectomy.